First year students' construction of an academic identity in English as a foreign language - Angels Oliva Girbau; Marta Milian Gubern (Universitat Politècnica de València, 2013)
This paper studies the construction of an academic identity through writing in English as a  foreign language, using a theoretical approach based on socio-constructivism, genre theory, systemic-functional linguistics and cultural-historical activity theory. Specifically, we study the relationship between academic genres and identity in first-year Humanities students, and to what extent a reflective social approach to writing instruction can foster students' initiation by providing spaces to analyse and discuss the nature of the academic activity system. The theoretical underpinnings present students' identity in construction as an essential element in the process of acquisition of academic genres, hence key to students' success at university, and students' identities as key elements of the academic activity system, at the same level as the other three – its communication tools, users, and goals. The theoretical framework guided the design of a course on academic English as a foreign language for first-year Humanities students at Universitat Pompeu Fabra. The course materials were used simultaneously as research tools to gather the data for the study, using an emic perspective as a teacher/researcher. The results show a close relationship between students' problems with the acquisition of genres in English and conflicts between their identities and other elements of the academic activity system, particularly their relation to other members and to ideational content, and hence students' inability to make relevant contributions due to problems using academic genres in English.   RESUMEN Construcción de la identidad académica a través del inglés como lengua extranjera en alumnos de primero. El presente artículo estudia la construcción de la identidad académica a través de la escritura en inglés como lengua extranjera, desde la base teórica del socioconstructivismo, la teoría de género, la lingüística sistémico-funcional y la teoría de actividad histórico-cultural. Concretamente, se analiza la relación entre los géneros académicos y la identidad académica en alumnos de primero de Humanidades, y hasta qué punto un planteamiento social reflexivo de la enseñanza de la escritura contribuye a mejorar la integración de los alumnos, proveyéndoles de espacios y herramientas para el análisis del sistema de actividad académico. Conceptualizamos la identidad en construcción de los aprendices como un elemento esencial del proceso de adquisición de los géneros académicos, y por tanto clave para su permanencia en la universidad. Las identidades de los estudiantes son vistas como elementos clave del sistema de actividad académico, al mismo nivel que sus otros componentes – herramientas de comunicación, usuarios y metas. A partir de este marco, se diseñó un curso de inglés para usos académicos para alumnos de primero de Humanidades en la Universidad Pompeu Fabra (Barcelona). Los materiales del curso se usaron como herramientas para recoger datos para un estudio émico, evidenciando la relación entre los problemas de los estudiantes con la adquisición de géneros académicos en inglés y los conflictos que experimentan cuando sus propias identidades entran en contradicción con elementos del sistema, particularmente en relación con otros miembros del sistema y con el contenido del campo, lo que dificulta que los alumnos puedan construir conocimiento a través de los géneros en inglés.